Mobile Learning Business Model Framework - Nasiri, Alireza (Information Management and Business Review, 2014)
M-learning has become more and more important but still is a young educational and economical (Edu-Eco) technology. M-learning strategies are aimed at economic, academic and technological objectives, however they lack in modeling ensured economic measurements in the sense of profitable products. Throughout this paper, we discuss the prime categories of elements that participate in the m-learning value net and give an overview of their business models. In addition to considering the mobile and e-learning business, business models, we deconstruct the m-learning value net, and also use a literature review in order to identify different actors in a business model for M-learning.